(untitled) (Swiss Medical Weekly, 2020)
Hepatocellular carcinoma (HCC) is the most frequent primary malignancy of the liver. HCC is characterised by a heterogeneous clinical presentation. Liver cirrhosis is the most important risk factor for HCC. Regular surveillance with ultrasound examinations allows detection of HCC at an early stage, where curative treatment options such as surgical resection, liver transplantation and local ablative therapies can be applied. More advanced tumours are treated with transarterial chemo- or radiotherapy, and with systemic treatments including immunotherapies. Treatment decisions are based on tumour staging and liver function, and should be made in specialised interdisciplinary tumour boards. This expert opinion statement by the Swiss Association for the Study of the Liver reviews the current state of HCC management and provides recommendations adapted to the health care environment in Switzerland.